Research on the Impact of Enterprise Green Development Behavior: A Meta-Analytic Approach - Xingwei Li; Jiachi Dai; Jingru Li; Jinrong He; Xiang Liu; Yicheng Huang; Qiong Shen (Behavioral Sciences, 2022)
The environmental situation is not optimistic. Improving the level of enterprise green development behavior can help enterprises to comply with the trend of environmental protection. However, existing studies do not explain the factors influencing enterprise green development behavior. This research collects and screens 33 empirical studies related to enterprise green development behavior from multiple authoritative data platforms, which cover 10 different countries and regions. A quantitative approach is then used to comprehensively explore the influencing factors, deeply dig into their degree of influence, and explore the moderating effect of the moderators. The results show the following: (1) corporate tangible resources, corporate intangible resources, market environment, policy and institutional environment, and public supervision have positive effects on enterprise green development behavior, and there are differences in the degree of influence; (2) corporate intangible resources have the most significant influence on enterprise green development behavior; (3) the size, region, and industry of enterprise can moderate enterprise green development behavior. This research suggests four participants: society, enterprise, market, and government. The research results are intended to provide a basis for researchers to further study enterprise green development behavior for specific industries and promote enterprise green development.